Current Feed-forward Control for Buck Converter Based on Extended Kalman Filter - LI Hao; LIU Haitao; GAN Weiwei; ZHONG Yuan; DING Leilei; DU Chao (Kongzhi Yu Xinxi Jishu)
In order to improve the response speed of Buck converter to load mutation, it proposed an inductive current feed-forward control algorithm based on extended Kalman filter (EKF). Based on Buck converter state equation, an inductor current predictor was established based on EKF and the predicted inductor current was compensated for the given current to improve the effect of load current variation on the output voltage. Simulation results show that the method can restrain the load disturbance and control the output voltage (DC 600 V) fluctuating within ±20 V at the 50% load cast and 50% load remove.